Adelotremus leptus, a new genus and species of sabertooth blenny from the Red Sea (Teleostei: Blenniidae: Nemophini) - Smith-Vaniz, William F.; Rose, Jean Michel (Zootaxa, 2012)
Adelotremus leptus is described as a new genus and species of blenniid fish based on a single gravid female, 35.4 mmstandard length, collected from a polychaete tube in 15 m depth in the Red Sea near Sharm el Sheikh, Egypt. The genusdiffers primarily from other nemophin genera (except Xiphasia) in having pterygiophores of the dorsal-fin spines broadlycontacting robust vertebral neural spines, and the combination of dorsal-fin spines and rays IX, 19, total vertebrae 32,ventral margin of gill opening opposite dorsalmost 5th or 6th pectoral-fin ray and no lateral line. An identification key is provided for genera of the blenniid tribe Nemophini.